2022
DOI: 10.1162/rest_a_00955
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Willingness to Lead: Does the Gender Composition of Teams Matter?

Abstract: We explore how team gender composition affects willingness to lead by randomly assigning participants in an experiment to male- or female-majority teams. Irrespective of team gender composition, men are substantially more willing than women to lead their team. The pooled sample, and women separately, are more willing to lead female- than male-majority teams. An analysis of mechanisms reveals that a large share of the negative effect of male-majority teams on women's leadership aspirations is accounted for by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 63 publications
2
24
0
Order By: Relevance
“…Sample size limitations and the relative shortage of women in our study population prevented us assigning groups with token men. Previous laboratory work suggests that men in female-dominated settings do not face the same disadvantages as women in male-dominated settings (Born et al, 2020;Karpowitz and Mendelberg, 2014;Ott, 1989), but to our knowledge this has not yet been tested in a field experimental setting. Furthermore, to what extent are our results driven by the 1F woman being the lone woman versus just being outnumbered?…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Sample size limitations and the relative shortage of women in our study population prevented us assigning groups with token men. Previous laboratory work suggests that men in female-dominated settings do not face the same disadvantages as women in male-dominated settings (Born et al, 2020;Karpowitz and Mendelberg, 2014;Ott, 1989), but to our knowledge this has not yet been tested in a field experimental setting. Furthermore, to what extent are our results driven by the 1F woman being the lone woman versus just being outnumbered?…”
Section: Discussionmentioning
confidence: 81%
“…This leads to outcomes such as gender disparities in leadership because women correctly presume they will have less support from their team when men are in the majority (Born et al, 2020), women taking and getting less credit for joint work with men (Isaksson, 2018;Sarsons, 2017;Koffi, 2020), and women doing more of the "non-promotable" tasks in groups (Babcock et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…men are more likely than women to make the opening offer and men fight harder when left out from a coalition. As such, we contribute to the vast experimental economics literature on gender differences which has found that men are more inclined to enter competitions (Niederle and Vesterlund, 2007), contribute ideas (Coffman, 2014), lead a team (Born et al, 2020), or give advice on how to play strategically (Cooper and Kagel, 2016). Importantly, by now, it is also a robust finding that women's decision-making is influenced by gender stereotypes, as well as by gender composition, when the domain is stereo-typically perceived as disadvantageous for women (Coffman, 2014;Bordalo et al, 2019;Geraldes, 2020).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Women are more interested in keeping others from having power over them than they are in elevating themselves over others (Gruenfeld, 2020). Born et al (2020) found that men were substantially more willing than women to lead their team. Lewis and Krishnan (2004) showed that women had less power than men had.…”
Section: Gm 371mentioning
confidence: 99%